In Vivo-Expressed Genes of Pasteurella multocida - Hunt, Meredith L. (American Society for Microbiology, 2001)
Pasteurella multocida is the causative agent of infectious diseases of economic importance such as fowl cholera, bovine hemorrhagic septicemia, and porcine atrophic rhinitis. However, knowledge of the molecular mechanisms and determinants that P. multocida requires for virulence and pathogenicity is still limited. To address this issue, we developed a genetic expression system, based on the in vivo expression technology approach first described by Mahan et al. (Science 259:686–688, 1993), to identify in vivo-expressed genes of P. multocida. Numerous genes, such as those encoding outer membrane lipoproteins, metabolic and biosynthetic enzymes, and a number of hypothetical proteins, were identified. These may prove to be useful targets for attenuating mutation and/or warrant further investigation for their roles in immunity and/or pathogenesis.